(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Increasingly throughout the India, medical colleges are realising that they need to provide their students with adequate time and resources for learning ethics. Ethics is and always has been an essential component of medical practice. Ethical principles such as a respect for patients, informed consent and confidentiality are basic to physician patient relationship. In this cross sectional study, total 150 Medical students from 2nd Year and 3rd Year MBBS were participated from Government Medical College, Vadodara during year of 2018. Study format includes questionnaires like Multiple Choice Questions (MCQs) will be given to participants and will evaluate their answers. In our study it was found that the awareness and knowledge of medical ethics is more in 3rd year students in comparison to 2nd year students.The study of ethics prepares medical students to recognize difficult situations and to deal with them in a rational and principled manner. Ethics is also important in physicians’ interactions with society and their colleagues and for the conduct of medical research.